2019
DOI: 10.1186/s12909-019-1681-0
|View full text |Cite
|
Sign up to set email alerts
|

Methods for teaching evidence-based practice: a scoping review

Abstract: Background This scoping review aims to gather and map inspiration, ideas and recommendations for teaching evidence-based practice across Professional Bachelor Degree healthcare programmes by mapping literature describing evidence-based practice teaching methods for undergraduate healthcare students including the steps suggested by the Sicily Statement. Methods A computer-assisted literature search using PubMed, Cinahl, PsycINFO, and OpenGrey covering health, education a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(102 citation statements)
references
References 93 publications
5
90
0
7
Order By: Relevance
“…Instead, librarians work as equal partners with faculty members to embed IL into the course over its duration (Hoffman, Beatty, Feng, & Lee, 2017). Embedded librarians can offer support to students with developing their searching competency and with critically appraising the information they find (Larsen, Terkelsen, Carlsen, & Kristensen, 2019).…”
Section: Information Literacymentioning
confidence: 99%
“…Instead, librarians work as equal partners with faculty members to embed IL into the course over its duration (Hoffman, Beatty, Feng, & Lee, 2017). Embedded librarians can offer support to students with developing their searching competency and with critically appraising the information they find (Larsen, Terkelsen, Carlsen, & Kristensen, 2019).…”
Section: Information Literacymentioning
confidence: 99%
“…Embedding EBP in undergraduate nursing programs has been strongly recommended [ 18 ]. Earlier systematic reviews have been focused on the effectiveness of EBP teaching strategies for undergraduate health students [ 19 , 20 , 21 , 22 ], while other reviews focused on nursing students have exclusively focused on the effectiveness of EBP teaching methods to promote students’ critical thinking [ 23 ], without quantifying the effect of the strategies [ 12 , 13 ] or being oriented to qualitative studies [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…A more recent review, including 85 controlled trials of evidence-based practice interventions, found that some aspects of evidence-based practice (EBP) such as critical appraisal were focused on more, and there was a lack of high-quality instruments to measure outcomes 11. A further mapping review of undergraduate EBM teaching in various health disciplines found a focus on teaching critical appraisal and integrating appraised evidence but a lack of evaluation 12. Educational packages and instruments which address all EBP steps are, therefore, still much needed.…”
Section: The Evidence For Teaching Ebm and Ebhcmentioning
confidence: 99%